Evaluation of immunological, inflammatory, and oxidative stress biomarkers in gasoline station attendants - Moro, Angela Maria; Sauer, Elisa; Brucker, Natália; Charão, Mariele Feiffer; Gauer, Bruna; do Nascimento, Sabrina Nunes; Goethel, Gabriela; Duarte, Marta Maria Medeiros Frescura; Garcia, Solange Cristina (BMC pharmacology & toxicology, 2019)
Gasoline is a complex mixture of saturated and unsaturated hydrocarbons, in which aromatic compounds, such as BTX (benzene, toluene, and xylene) feature as the main constituents. Simultaneous exposure to these aromatic hydrocarbons causes a significant impact on benzene toxicity. In order to detect early alterations caused in gasoline station attendants exposed to BTX compounds, immunological, inflammatory, and oxidative stress biomarkers were evaluated. A total of 66 male subjects participated in this study. The gasoline station attendants (GSA) group consisted of 38 gasoline station attendants from Rio Grande do Sul, Brazil. The non-exposed group consisted of 28 subjects who were non-smokers and who had no history of occupational exposure. Environmental and biological monitoring of BTX exposure was performed using blood and urine. The GSA group showed increased BTX concentrations in relation to the non-exposed group (p < 0.001). The GSA group showed elevated protein carbonyl (PCO) levels and pro-inflammatory cytokines, decreased expression of CD80 and CD86 in monocytes, and reduced glutathione S-transferase (GST) activity compared to the non-exposed group (p < 0.05). BTX levels and trans,trans-muconic acid levels were positively correlated with pro-inflammatory cytokines and negatively correlated with interleukin-10 contents (p < 0.001). Increased levels of pro-inflammatory cytokines were accompanied by increased PCO contents and decreased GST activity (p < 0.001). Furthermore, according to the multiple linear regression analysis, benzene exposure was the only factor that significantly contributed to the increased pro-inflammatory cytokines (p < 0.05). Taken together, these findings show the influence of exposure to BTX compounds, especially benzene, on the immunological, inflammatory, and oxidative stress biomarkers evaluated. Furthermore, the data suggest the relationship among the evaluated biomarkers of effect, which could contribute to providing early signs of damage to biomolecules in subjects occupationally exposed to BTX compounds.